(untitled) (Journal of International English Research Studies (JIERS), ISSN: 3048-5231, 2025)
This study investigates the impact of technology-enhanced language learning (TELL) within virtual classroom environments in Japan and Germany, focusing on cross-cultural differences in pedagogical practices, learner engagement, and technological integration. Drawing on data from language learners and instructors in both countries, the research employs a mixed-methods approach combining surveys, interviews, and classroom observations. Findings reveal that while both contexts benefit from digital tools such as video conferencing platforms, learning management systems, and interactive language apps, cultural attitudes toward technology, teacher-student interaction styles, and institutional support significantly influence the effectiveness of virtual language instruction. Japanese classrooms emphasize structured learning and teacher authority, leading to high technical compliance but limited spontaneous interaction. In contrast, German classrooms favor learner autonomy and open discussion, fostering greater student-led use of digital tools. The study underscores the importance of culturally responsive design in TELL and offers recommendations for optimizing virtual language learning across diverse educational contexts.